Bathymetry-constrained warm-mode melt estimates derived from analysing oceanic gateways in Antarctica - L. Nicola; L. Nicola; R. Reese; R. Reese; M. Kreuzer; M. Kreuzer; T. Albrecht; T. Albrecht; R. Winkelmann; R. Winkelmann; R. Winkelmann (The Cryosphere)
Melting underneath the floating ice shelves surrounding the Antarctic continent is a key process for the current and future mass loss of the Antarctic Ice Sheet. Troughs and sills on the continental shelf play a crucial role in modulating sub-shelf melt rates, as they can allow or block the access of relatively warm, modified Circumpolar Deep Water to ice-shelf cavities. Here we identify potential oceanic gateways in at least 7 out of 19 regions subdividing the Antarctic continent that could channel warm water masses to Antarctic grounding lines, based on access depths inferred from high-resolution bathymetry data. We analyse the properties of water masses that are currently present in front of the ice shelf and that might intrude into the respective ice-shelf cavities in the future in case of changes in the ocean circulation. We use the ice-shelf cavity model PICO to estimate an upper bound of melt rate changes in case offshore, intermediate-layer warm water masses gain access to the cavities. Depending on the presence of an oceanic gateway and the current ice-shelf melt conditions, we find up to 42-fold larger basal melt rates. The identification of oceanic gateways is thus valuable for assessing the potential of ice-shelf cavities to switch from a cold to a warm state, which could result in widespread ice loss from Antarctica.